Developing proficiency in pedagogical integration of emerging technologies: an educational design research of a community of practice at Makerere University - Walimbwa, Michael (School of Education, 2018)
This thesis investigated the development of proficiency in pedagogical integration of emerging technologies amongst educators at Makerere University. Limited educator CoPs focused on pedagogical integration of ETs inhibit educator potential to contribute to quality learning through pedagogical integration of ETs. The general question in this thesis is how social architecture in an educator CoP provides opportunities for enhancing proficiency development in pedagogical integration of ETs. Based on educational design research framework and situated learning theory, a community of practice as an intervention was designed and implemented between 2014 and 2016. Data was collected through observations, focused discussions and interviews from five educators who actively participated. An interpretive thematic analysis was done from which findings indicate that a social architecture in community of practice enables educators to initially accept that they are less experienced and potential members and then, join forces in a community to take charge of their transformation process. A social architecture enables drawing on individual talent and exploiting synergy between individuals with varying experiences; the process also comprises specific actions and engagements, which when shared in a social environment help motivate, inspire and evoke emulation of a practice. A community of practice provides an ideal context that enable educators to be more honest in evaluating their own technology skills and gaining confidence in seeking to develop skills. Pedagogical integration of emerging technologies is a practice highly influenced by individual attitudes in a social environment. In communities of practice faced with resource-constraints, the constantly evolving technologies, limited mentorship capacity, and mind-set are among the inhibitors in the social architecture that contributes to proficiency development in pedagogical integration of emerging technologies. This thesis concludes that social architecture in a community of practice contributes to the process of developing proficiency in pedagogical integration of emerging technologies. The design principles that emphasize configuration of a social architecture like interactions, networks and collaborations among educators are helpful in pedagogical integration of emerging technologies. It is therefore recommended that a social architecture in a community of practice be exploited by educators to enhance pedagogical integration of emerging technologies. The original contribution of this thesis is coming up with new design principles and theoretical insights related to a social architecture in a community of practice focused on pedagogical integration of emerging technologies.